ACOUSTIC OBJECT LOCATING SYSTEM USING TRIANGULATION METHOD - HAMZAH, HAZILAH (Universiti Teknologi Petronas, 2011)
In this paper we study the acoustic object locating system using triangulation method. This system consists of a set of acoustic sensors aligned in a straight line with equal distance apart. The sound intensity is measured by the acoustic sensor at different positions. Since the distance between the source and the sensors vary, the location of the source can be determined by the discrepancy of the intensity measured using triangulation method. The location of the source is then displayed on the plan position indicator. This report will be discussed about the background study, problem statement, objectives, and scope of study. In Chapter 2 we derive the key formula for the coordinate of the source of acoustic object. We then design the circuit based on the underlying concept. In Chapter 4, we apply programming in the system and show how the coordinate of the source will be displayed on the plan position indicator.